Type-2 epithelial-mesenchymal transition in oral mucosal nonneoplastic diseases - Meng, Zhaosong; Yang, Tianle; Liu, Dayong (Frontiers in Immunology, 2022)
Oral mucosa is a membranous structure composed of epithelial and connective tissue covering the oral cavity. Oral mucosa served as the first immune barrier to defend against pathogens for systemic protection. It is frequently exposed to mechanical abrasion, chemical erosion and pathogenic invasion, which result in oral mucosal lesions, especially inflammatory diseases. EMT is confirmed as a crucial biological process in the pathogenesis of oral mucosal disorders, which is divided into three types (Type-1,2,3) according to different physiological consequences. Among them, type-2 EMT usually plays a vital role in wound repair, organ fibrosis and tissue regeneration and causes various infectious and dis-infectious immunological diseases such as oral lichen planus, oral leukoplakia, oral submucosal fibrosis and other precancerous lesions. However, the mechanism and cognition between type-2 EMT and oral mucosal inflammatory disorders have not been fully established. This review firstly provides a comprehensive evaluation of type-2 EMT in the oral mucosal diseases via chronic inflammatory microenvironment, aiming to lay a foundation for further explorations and put forward possible treatments in the future.